A promising problem : the new Chicana/o history - Blanton, Carlos Kevin, 1970- (University of Texas Press, 2016)
Chicana/o history has reached an intriguing juncture. While academic and intellectual studies are embracing new, highly nuanced perspectives on race, class, gender, education, identity, and community, the field itself continues to be viewed as a battleground, subject to attacks from outside academia by those who claim that the discipline promotes racial hatred and anti-Americanism. Against a backdrop of deportations and voter suppression targeting Latinos, A Promising Problem presents the optimistic voices of scholars who call for sophisticated solutions while embracing transnationalism and the reality of multiple, overlapping identities. Showcasing a variety of new directions, this anthology spans topics such as growth and reassessment in Chicana/o history manifested in a disruption of nationalism and geographic essentialism, the impact of legal history, interracial relations and the experiences of Latino subpopulations in the US South, race and the politics of religious history, transborder feminism in the early twentieth century, and aspirations for a field that increasingly demonstrates the relational dynamics of cultural production. As they reflect on the state of their field, the contributors offer significant insights into sociology, psychology, anthropology, political science, education, and literature, while tracing the history of activism throughout the last century and debating the very concepts of "Chicano" and "Chicano history." Although the political landscape is fraught with closed-off rhetoric, A Promising Problem encourages diversity of thought and opens the possibilities of historical imagination.